SISTEM INFORMASI PENJUALAN SEPEDA MOTOR HONDA PADA SALES OFFICE WELERI - Edy Siswanto; Dendy Kurniawan; Munifah Munifah (Universitas Sains dan Teknologi Komputer, 2023)
Technology and science are currently developing very rapidly, so that every business world, organization and other fields need fast, accurate and precise information. The data obtained will be distributed evenly so that it can fulfill information requests. The use of computer technology in business or office environments, both government and private, is no longer something strange. Especially in large companies, the use of it technology will help reduce workload. Astra motor weleri, a commercial company that sells honda brand motorbikes. Astra motor weleri is one of the largest dealers in kendal regency so there is quite a lot of stock at the dealer. With so many motorbikes in stock, stocking errors sometimes occur during the sales process, resulting in frequent cancellations of orders or what is usually called do delivery orders. Sellers also have difficulty marketing to consumers because consumers find it difficult to see automotive products. For example, a seller must send every photo to consumers who want to buy a car. According to the author, it is less effective. Apart from that, the car buying process from the consumer side is also too complicated because it takes a lot of time, both in cash and credit. With so many motorbikes being sold, using a manual sales system is deemed less effective.